Bruce Bronzan Campaign Celebrating At Fresno Hilton Skyroom - Watkins, Howard::::::::: (1982)
Demi McManus, Jim McManus, Betty Ramacher, Richard Ramacher sitting in booth Cigarettes and lighters on table